PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KARTU MASALAH UNTUK PENINGKATAN HASIL BELAJAR PPKN SISWA KELAS III SDN BINTORO 16 DEMAK - Selviana Vivi Nugraheni; Erik Aditia Ismaya; Wawan Shokib Rondli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this research is to describe the increase in student learning outcomes through the application of the Problem Based Learning model assisted by problem card media in Civics learning class III SDN Bintoro 16 Demak. The research method used is classroom action research. This research was conducted in two cycles, in each cycle there are stages of planning, action, observation, and reflection. The subjects of this study were class III students at SDN Bintoro 16 Demak with a total of 8 students. Sources of research data are teachers and students. The data collection techniques used included interviews, observations, tests, and documentation. The validity of the data used was expert judgment and data analysis using qualitative and quantitative data analysis. The results showed that the Problem Based Learning model assisted by problem card media could improve student learning outcomes in the aspects of knowledge, attitudes and skills. Learning outcomes aspects of knowledge have increased, in the first cycle to obtain 62.5% and in the second cycle increased to 87.5%. The learning outcomes of the attitude aspect experienced an increase from the first cycle to 68.22% in the second cycle to 84.90%. The learning outcomes of the skills aspect increased from cycle I to 75.77% in cycle II to 87.75%.